Positive Pattern of Antibiotic Sensitivity in Blood Cultures Disease Caused by a Typhoid - Maham Amin, Muqaddas Fatima, Samia Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study establish the antibiotic sensitivity pattern in blood culture positive typhoid illness. Study Design: Retrospective study Place and Duration: Mayo Hospital Lahore. April 2021-Dec 2021 Methods: There were a total of 98 male and female patients. Patients ranged in age from 8 to 60. After obtaining informed written permission, we collected demographic data on each patient, including age, gender, and BMI. All of the patients were suffering from a fever. All patients had their blood tested for the presence of salmonella species. Antibiotic susceptibility was determined using the Kirby Bauer Disc Diffusion technique and interpreted in compliance with National Committee for Clinical Laboratory Standards (NCCLS) standards. SPSS 24.0 was used to analyse all of the data in the study. Results: Among 98 patients, 61(62.2%) were males and 37 (37.8%) females. Majority of the patients 38 (38.8%) were from age group 21-30 years. Frequency of typhi 69 (70.4%) was greater than that of paratyphi 29 (29.6%). According to our research findings, Azithromycin, chloramphernicol, cotrimoxazole, genramycin, and azithromycin all had better sensitivity than ciprofloxacin and ofloxacin (10.2%, vs 7.1%) . However, both medications have a significant level of resistance. Salmonella typhi was resistant to 91(92.9 %) of the nalidixic acid tested. Conclusion: We found a wide range of antimicrobial sensitivity patterns, including exceptionally high sensitivity to antibiotics like chloramphenicol and cotrimoxazole that have been used in the past. Quinolones, which have been extensively used in the previous two decades, have been shown to have an extremely low sensitivity.